Molecular Identification of Dermo-Mycotic Infection and the Effect of Dietary-Essential Oils on Broiler Chickens in Upper Egypt - Mokhtar, Aml; Moharram, Ahmed M.; Nassar, Ahmed Y. (Journal of Advanced Veterinary Research, 2023)
The importance of searching for natural alternatives away from chemicals in poultry health and treatment has benefits for humans in many directions, as we control the bad effect of the accumulation of harmful chemicals in their meat, as well as reduce the risk of zoonotic infection and preserve the environment from chemical pollution. Enormous fungi induce a considerable level of annihilation in the poultry industry and human consumers due to their zoonotic implications. This study is designed to explore the effects of keratogenic and toxigenic skin fungal affection and the effects of dietary-essential oils in broilers -chicken (n-120). Skin scrapings and feather samples were examined mycologically in association with PCR sequencing for genomes of the culturally detected fungi (in South Korea) based on phylum tree and all Sequences data was deposited in GenBank and each was assigned an accession number. Sera samples of the tested broilers were examined by ELIZA against biogenic amine mainly histamine during the summer season, also a histopathological examination of skin sections before and after taking feed additives (essential oils) as anti-fungal for thirty days, the broiler-fed diet was supplemented with peppermint, thyme, and Carvacrol 70 mg/kg (w/w) in dietary feed. The isolated fungi were: Fifteen fungal species belonging to 9 genera of filamentous fungi which were isolated from skin scrapings and feathers of chickens. Aspergillus niger and A. flavus are the most prevalent species (20 samples representing 100% of total samples for each. Rhizopus oryze 20% and Fusarium oxysporum 15% were cultured from total samples respectively. Four fungal species appeared in 10% of the tested samples which are Aspergillus qudrilineatus, Paecilomyces variotii (Byssochlamys spectabilis), Scopulariopsis brevicaulis and Exserohilum rostratum. Finally, the other seven fungi presented as 5% from tested samples. The average level of serum histamine before treatment was 16.6 ng/ml and after feeding was 12.3 ng/ml (significant decrease, P < 0.05) referring to the significant role of the essential oils in broilers ration.